Social Emotional Learning in Schools: Perceptions of Secondary School Teachers in Swat, Pakistan - Hussain, Akhtar; Ahmad, Dr Nasir; Khan, Dr Farooq Nawaz; Hussain, Dr Sajjad; Muhammad, Wafa; Kamal, Asif Ahmad; Nazli, Farkhanda (ACADEMIA International Journal for Social Sciences, 2025)
The research examines the understanding of Social Emotional Learning (SEL) among secondary school teachers within Swat Pakistan while recognizing the importance of this education aspect. Teachers in a region that deals with political instability alongside traditional education systems and little emotional expression must have their views about Social Emotional Learning examined because it is both urgent and crucial to understand. Data retrieval occurred through structured validated questionnaires sent to 200 secondary school teaching staff who worked at both public and private educational institutes. The survey evaluated teachers' knowledge of SEL as well as their understanding and problems they encounter when working with SEL through a five-point Likert scale. Research results indicate teachers show both adequate and advanced comprehension about SEL ideas when showing favorable stances regarding its classroom integration. The staff members encounter moderate integration barriers that stem from inadequate training procedures together with insufficient institutional backing and formal curriculums that are hard to adapt and social cultural restrictions. The study demonstrated that female and veteran teachers together with private school educators presented better awareness with favorable perceptions but public school educators encountered more implementation barriers. An analysis of correlations revealed that raising teacher understanding combined with positive attitudes directly corresponds to lower obstacles in implementing social and emotional learning programs. This demonstrates the critical value of developing teaching staff abilities to achieve effective SEL practice.Teachers clearly understand SEL's significance for emotional intelligence development and interpersonal skills building besides creating supportive classroom environments yet they encounter substantial obstacles implementing those approaches. The research suggests that teachers need proper SEL education during training and the development of culturally appropriate frameworks while the government must revise educational policies and give supporting institutions. This study strengthens the debate about social-emotional learning in developing and post-conflict contexts by providing practical guidance for teachers and policy makers who want to develop emotional and social competencies in Pakistani schools.